2014
DOI: 10.1002/cncy.21428
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intraoperative cytological assessment of bone resection margins in patients with oral squamous cell carcinoma

Abstract: BACKGROUND:Frozen sections are routinely applied to control for adequate resection margins. In cases in which carcinoma infiltrates bone, the intraoperative microscopic assessment of bone margins remains challenging due to technical difficulties to section native bone. The objective of the current study was to evaluate an intraoperative cytological approach to control bone resection margins in patients with bone-infiltrating oral squamous cell carcinomas. METHODS:A total of 174 cytological preparations obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…Their study concluded the sensitivity and specificity of touch imprint cytology as 95.3% and 96% respectively. The positive predictive value, negative predictive value and diagnostic accuracy of their study came out to be 93.8, 96.9 and 95.7% respectively [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their study concluded the sensitivity and specificity of touch imprint cytology as 95.3% and 96% respectively. The positive predictive value, negative predictive value and diagnostic accuracy of their study came out to be 93.8, 96.9 and 95.7% respectively [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, Nieberler et al described a method for cytological assessment, in which specimen margins were scraped, placed onto slides, stained, and assessed by cytopathologists. 6 Through this method, they obtained a sensitivity of 94.4% and sensitivity of 97.5% through a reasonably short specimen preparation and assessment process. This was the first approach for assessing cortical bone specimens, though described limitations included specimen desiccation, insufficient material, and low quality cytologic preparations due to the presence of blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…3,5 Unlike soft tissue, bone resection margins are not obtainable through frozen sections, due to high mineral content. 6 Therefore, histopathological confirmation of the presence of tumor cells is only available days after surgery. 5,6 Despite the importance of margins, and the long latency of traditional histopathological methods, there remain few alternatives for intraoperative assessment of resection margins during mandibulectomy other than conventional visual inspection and palpation, which may be inadequate in many cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No full cross-section analysis, risk of missing infiltrated areas, presence of scattered tumour cells due to operation Nieberler et al [27] Cytological analysis cells obtained by a cytobrush Accelerated fixation and decalcification…”
Section: Immunohistochemistry (Ihc) Staining Keratin 5/6mentioning
confidence: 99%